STUDYING LITERARY MATERIALS BASED ON BLLOM’S TAXONOMY IN CLASSES CONDUCTED IN LANGUAGES OTHER THAN THE MOTHER TONGUE - Mambetova Gulchexra Abibullaevna (Researchparks Publishing, 2023)
In this article, ways of using Blum's taxonomy in teaching Karakalpak literature materials in classes where education is conducted in languages other than the state language were studied based on T. Qayipbergenov's work